Estudo sobre a síntese e caracterização de clusters binários e ternários de organocalcogenetos contendo metais de transição - Back, Davi Fernando (2008)
This work presents a study related to the synthesis and characterization of a series of clusters with chacogen-metal bonds in which the metals are mercury, silver, cobalt, nickel, palladium, cadmium and zinc. The synthetic strategy is based on the combination a building block, bis-(phenyltellurium)mercury(II), (Hg(TePh)2), as the starting material, with a series of co-ligands and metal salts. In the synthesis of the fourteen clusters presented in this work, evidence of redistribution reactions was observed and, for some syntheses, disproportion reactions occurred concomitantly. In this study the following clusters were obtained: [Hg5(PhTe)7Br3]n;[Hg6(PhTe)15Te2Ag4]n; [Hg4(TePh)7IPy]n;[Hg4(SePh)7IPy]n;[Hg8(TePh)14Te(PPhMe2)2]·DMF; [Hg11(TePh)18Te2(Py)3]·Py2;[Hg6(PhTe16)Ag4];[Hg2(TePh)4Ag2(Cl2)]n; [Hg6(TePh)16Ag4Py4]·H2O;[Hg8Te(TePh)12Cl4]-2[Ni(DMF)6]+2; {[Zn(H2O)2(OH)2]@[Hg16(TePh)32]};[Pd2(TePh)2Cl2(PPh3)2]; [Hg8Te(TePh)12Cl4]-2[Co(DMF)6]+2 and {[Cd(H2O)2(OH)2]@[Hg16(TePh)32]}. The clusters were characterized by single crystal X-ray diffraction, elemental analysis and electron microscopy with X-ray dispersive energy spectroscopy. For some clusters, thermogravimetric analysis was carried out to test their stability.